The correlation between physical activity and psychological resilience in young students: a systematic review and meta-analysis - Qiu, Wentao; Huang, Chao; Xiao, Haibin; Nie, Yuyang; Ma, Wenxue; Zhou, Fangbing; Liu, Cong (Frontiers in Psychology, 2025)
ObjectiveAgainst the backdrop of increasing social stress and a faster pace of life, psychological resilience as a key psychological attribute has become increasingly prominent. Physical activity is also a significant factor influencing the psychological resilience of young students. This study aims to systematically review the research progress on the relationship between physical activity and psychological resilience among young students. It analyzes the correlation between the two and the influencing factors, and explores the mechanisms by which physical activity among young students contributes to psychological resilience. The objective is to motivate young students to engage more actively in physical activities, thereby enhancing their psychological resilience.MethodsFollowing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement, an extensive literature search was conducted across six electronic databases: Web of Science, PubMed, ProQuest, Scopus, ScienceDirect, and EBSCOhost. The search spanned from January 1, 2000, to November 20, 2024. The selected studies were subjected to rigorous quality evaluation, and relevant methodological and outcome data were extracted using a standardized data extraction form. Subsequently, meta-analysis of the included studies was performed using Stata 18 software, including heterogeneity testing and assessment of publication bias.ResultsAfter literature screening, a total of 21 studies were included, exploring the correlation between physical activity and psychological resilience. These studies employed Pearson correlation analysis (14 studies), multiple regression analysis (13 studies), and structural equation modeling (SEM) (eight studies). Using a random-effects model to combine effect sizes, the average correlation coefficient was 0.249 (p < 0.001), the average standardized coefficient for the promotion of psychological resilience by physical activity was 0.195 (p < 0.001), and the average path coefficient for the enhancement of psychological resilience through physical activity was 0.205 (p < 0.001).ConclusionThis study found a significant positive correlation between physical activity and psychological resilience among young students, with physical activity exerting a positive impact on psychological resilience. Similarly, psychological resilience plays a promotional role in the participation of young students in physical activities.